Business Strategies, Competition, and Regulation in Enhancing MSME Sustainability in East Java - Sundari, Ariefah; Armanu, Armanu; Indrasari, Meithiana; Sukesi, Sukesi (Westscience Press, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are central to Indonesia’s economy, contributing more than 60% of GDP and employing the majority of the workforce. In East Java, MSMEs account for nearly 59% of regional GDP, underscoring their critical role in inclusive growth. Despite this importance, MSMEs face persistent challenges, including limited access to credit, low digital adoption, weak innovation, and vulnerability to competition. While prior studies have explored these factors separately, few have developed an integrative framework linking business strategies, competition, and regulation to sustainability. This study examines the effects of seven strategic dimensions, credit facilities, digital marketing, innovation, pricing, distribution, circular economy, and inclusive partnerships, on MSME sustainability. Business competition is tested as a mediating variable and regulation by the Indonesian Competition Commission (KPPU) as a moderating variable. Data were collected from 396 MSMEs across handicrafts, food and beverage, and service sectors, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results show that digital marketing, innovation, pricing, distribution, and inclusive partnerships significantly enhance sustainability, while credit facilities and circular economy practices have limited direct impact. Competition mediates the effects of strategies on sustainability, and regulation strengthens both strategic and competitive impacts. The study contributes theoretically by integrating Resource-Based View, Competitive Advantage, Institutional Theory, and Circular Economy perspectives into a holistic model, and provides practical insights for policymakers and MSME actors seeking to enhance resilience and long-term sustainability.